The regulatory role of dietary factors in skeletal muscle development, regeneration and function. Issue 3 (27th January 2022) - Wang, Liyi; Xu, Ziye; Ling, Defeng; Li, Jie; Wang, Yizhen; Shan, Tizhong
Abstract: Skeletal muscle plays a crucial role in motor function, respiration, and whole-body energy homeostasis. How to regulate the development and function of skeletal muscle has become a hot research topic for improving lifestyle and extending life span. Numerous transcription factors and nutritional factors have been clarified are closely associated with the regulation of skeletal muscle development, regeneration and function. In this article, the roles of different dietary factors including green tea, quercetin, curcumin (CUR), eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and resveratrol (RES) in regulating skeletal muscle development, muscle mass, muscle function, and muscle recovery have been summarized and discussed. We also reviewed the potential regulatory molecular mechanism of these factors. Based on the current findings, dietary factors may be used as a potential therapeutic agent to treat skeletal muscle dysfunction as well as its related diseases.